Induced reproduction of dourado (Salminus brasiliensis): fertilization with sperm cryopreserved in ACP®-104 - Zanandrea, Ana Carolina Volpato; Weingartner, Marcos; Zaniboni-Filho, Evoy (Acta Scientiarum. Animal Sciences, 2016)
Experiments were conducted to improve the fertilization rate of cryopreserved semen of dourado, Salminus brasiliensis. The experiment tested two cryoprotectant solutions at different semen: cryoprotectant ratios (1:5, 1:15, 1:25 and 1:50). The standard solution for the species (mixture of dimethyl sulfoxide, glucose, egg yolk and distilled water) was compared to a 350 mOsm ACP®-104 solution, which is composed of powdered coconut water diluted in distilled water and methylglycol. Differences between the dilutions tested were significant only for ACP®. The fertilization potential by using the standard solution at the lowest dilution (1:5) is equated when the sperm is diluted in ACP® at 1:25 or 1:50. These results show that the standard solution is the most suitable for the cryopreservation of dourado sperm, since the dilution did not alter the fertilization rate, requiring smaller storage space.